O uso de sistemas de limpeza de baixa toxicidade para o restauro de pinturas acrílicas sobre tela - Mariana Souza Barros Onofri (2024)
This research aims to study low-toxicity aqueous cleaning systems for restoring acrylic paintings on canvas using mockups. In addition, these systems will be compared to the first five formulations of the list of solvents proposed by Liliane Masschelein-Kleiner (1937-), which is still used by the community of conservators-restorers of movable and integrated cultural goods in Brazil. The physicochemical behavior of acrylic emulsion-based paints will be investigated, as well as their insertion in the Brazilian artistic context, with a brief history of the Acrilex® brand. The research will also cover the state of the art on the chemical cleaning process linked to conservation-restoration practices, the properties of the low-toxicity cleaning systems that will be used in practice - aqueous solutions with adjusted pH and ionic strength, microemulsions, silicone-based solvents and solvent gels - and a description of the solvents used by Masschelein-Kleiner in accordance with each one's safety data sheet. This will help to ensure that low-toxicity cleaning systems are included in the daily lives of conservation and restoration professionals and students.